2020
DOI: 10.1140/epja/s10050-020-00097-w
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of pionless effective field theory in the A-body sector

Abstract: Current models of inter-nucleon interactions are built within the frame of Effective Field Theories (EFTs). Contrary to traditional nuclear potentials, EFT interactions require a renormalization of their parameters in order to derive meaningful estimations of observable. In this paper, a renormalization procedure is designed in connection with many-body approximations applicable to large-A systems and formulated within the frame of many-body perturbation theory. The procedure is shown to generate counterterms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It has also been suggested that the scales of the chiral EFT interaction and the inherent scales of the many-body configuration space (e.g., IR and UV cutoffs inherited from a HO basis, see section 4.3) or coordinate space wave functions should not be treated independently, and that by doing so, current manybody approaches might at least contribute to power counting issues. There have been a few efforts to explore this problem, but more work is clearly required [315][316][317][318][319][320]. Application needs.…”
Section: Strengthening and Employing The Hierarchy Of Strong Interactmentioning
confidence: 99%
“…It has also been suggested that the scales of the chiral EFT interaction and the inherent scales of the many-body configuration space (e.g., IR and UV cutoffs inherited from a HO basis, see section 4.3) or coordinate space wave functions should not be treated independently, and that by doing so, current manybody approaches might at least contribute to power counting issues. There have been a few efforts to explore this problem, but more work is clearly required [315][316][317][318][319][320]. Application needs.…”
Section: Strengthening and Employing The Hierarchy Of Strong Interactmentioning
confidence: 99%
“…}; see, e.g., Refs. [35,36] for details. [If there are subdivergences the actual degree of divergence can be larger than d.] The MBPT diagrams are obtained from scattering diagrams by closing the external lines (and excluding occupied states in loop integrals) of a single scattering diagram, or by closing and connecting the external lines of several diagrams.…”
Section: Effective Field Theory For Nonrelativistic Fermionsmentioning
confidence: 99%
“…It has also been suggested that the scales of the chiral EFT interaction and the inherent scales of the many-body configuration space (e.g., IR and UV cutoffs inherited from a HO basis, see Section 4.3) or coordinate space wave functions should not be treated independently, and that by doing so, current many-body approaches might at least contribute to power counting issues. There have been a few efforts to explore this problem, but more work is clearly required [315,316,317,318,319,320].…”
Section: Strengthening and Employing The Hierarchy Of Strong Interact...mentioning
confidence: 99%